A probabilistic analysis of traffic separation in shared Ethernet systems using the h-BEB collision resolution algorithm - Ricardo Moraes (2005)
Ethernet is a widely used network technology, with a Medium Access Control protocol based on the collision detection between randomly initiated transmissions. It has a non-deterministic behaviour, due to the use of a probabilistic contention resolution algorithm, which impairs the support of real-time communications. In this paper, it is proposed the use of a modified algorithm for the collision resolution in shared Ethernet networks. Such algorithm, referred as high priority Binary Exponential Backoff (h-BEB), provides high priority traffic separation, enabling the support of real-time communications. It allows multiple Ethernet standard devices to coexist with one h-BEB modified station in the same network segment, imposing a higher priority for the transfer of h-BEB related traffic. The probabilistic analysis of traffic separation provided by the proposed algorithm shows that it guarantees an access delay significantly smaller for an h-BEB station, when compared with the access delay for BEB stations.